1987
DOI: 10.1103/physrevd.36.1905
|View full text |Cite
|
Sign up to set email alerts
|

Application of the real-time temperature Green’s functions to chiral-symmetry breaking and restoration

Abstract: The real-time temperature Green's functions are applied to study spontaneous breaking and restoration of chiral symmetry in quantum chromodynamics. In particular we discuss some salient features of the temperature Green's functions which essentially reflect the Kubo-Martin-Schwinger condition. The gap equation is given in the ladder approximation and solved with a rough approximation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In Refs. [7,9,10] and 8% against t F = 0.2 ∼ 0.6, respectively. These values of t F = 0.2 ∼ 0.6 correspond to those of the running coupling g 2 (p = k = 0) = 570 ∼ 92.6.…”
Section: Zero Chemical Potential Casementioning
confidence: 94%
See 1 more Smart Citation
“…In Refs. [7,9,10] and 8% against t F = 0.2 ∼ 0.6, respectively. These values of t F = 0.2 ∼ 0.6 correspond to those of the running coupling g 2 (p = k = 0) = 570 ∼ 92.6.…”
Section: Zero Chemical Potential Casementioning
confidence: 94%
“…[3,4,5,6] The Schwinger-Dyson equation in the improved ladder approximation is solved with further approximations and give the dynamical symmetry restoration. [7,8,9,10,11] Nambu-Jona-Lasinio models, as phenomenological models of QCD, provide us with useful pictures about the dynamical chiral symmetry breaking and its restoration. [12,13,14] In these three approaches it is indicated that there is a second order phase transition at (T, µ) = (T c , 0) and a first order one at (T, µ) = (0, µ c ) in the case of the two massless flavors.…”
Section: Introductionmentioning
confidence: 99%
“…Here the spinor two-point function S 11 (p) is given by evaluating the 1-1 matrix element of the expression [6,7] iS ab (p) = V (β, p)…”
Section: Schwinger-dyson Equation At Finite Temperaturementioning
confidence: 99%
“…There have been several works dealing with this problem in quantum chromodynamics. There have, however, been not many works [6,7,8] which have studied this question by taking into account of the photon mass coming from the hard thermal loop. Thus we try to present the thorough analysis of the chiral phase transition in Abelian gauge theories at finite temperature with due consideration on the hard thermal loop by using the Schwinger-Dyson equation.…”
Section: Introductionmentioning
confidence: 99%
“…(23) with respect to Σ(p E ) leads to Eq. (11) which is equivalent to the original equation (8) in the Higashijima-Miransky approximation apart from the two boundary conditions. We will take account of these conditions when we introduce the trial mass function.…”
Section: Effective Potential For the Quark Propagatormentioning
confidence: 99%